2022
DOI: 10.1177/10776990221142877
|View full text |Cite
|
Sign up to set email alerts
|

Selection, Trust, and the Effects of Cable News Consumption

Abstract: Using two experimental studies, we examine how the selection and consumption of cable news influences news consumers’ cognitive processing, attitudes, and policy preferences. As expected, participants overwhelmingly self-selected into an ideologically aligned cable news network. Then, ideologically congruent messaging from Fox News and MSNBC was likely to prompt higher levels of agreement and lower levels of disagreement for those with mid- and high levels of trust in their selected cable news network. Our fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Finally, our results provide an additional explanation for why people seek out news content. Extensive research has shown that political beliefs can play an important role relative to understanding people’s feelings toward journalists (Lee, 2010) and their willingness to use specific media content (Hoewe et al, 2022; Stroud, 2011). However, there is a need to step beyond simply examining party identification and political ideology (Stroud, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our results provide an additional explanation for why people seek out news content. Extensive research has shown that political beliefs can play an important role relative to understanding people’s feelings toward journalists (Lee, 2010) and their willingness to use specific media content (Hoewe et al, 2022; Stroud, 2011). However, there is a need to step beyond simply examining party identification and political ideology (Stroud, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which individuals hold favorable opinions toward journalists has been shown to be an important predictor of media use habits (Moy et al, 2004; Strömbäck et al, 2020). In general, this line of inquiry has looked at how feelings toward journalists (Moy et al, 2004) and trust in news media (Hoewe et al, 2022; Strömbäck et al, 2020) relate to media use. Although these are different concepts, the underlying logic for the correlations is the same.…”
Section: Feelings Toward Journalists and News Usementioning
confidence: 99%
“…This discomfort can be alleviated by paying attention to pro-attitudinal news and avoided by ignoring counter-attitudinal news because of confirmation bias (Garrett, 2009). In this study, participants negotiated a combination of favorable or unfavorable content and/or news sources, though communication scholars have often not made a "critical distinction" between trust in sources and trust in messages (Barnoy & Reich, 2022, p. 197; see also Hoewe et al, 2023). Given trust in sourcing can affect trust in messaging, communication research pioneers have warned that persuasion or believability cannot be fully understood without taking both elements into account (e.g., Asch, 1948).…”
Section: Introductionmentioning
confidence: 93%
“…In one study, Fox News was the only outlet that a majority of Republicans trusted; 20 other news sources were distrusted more than trusted, especially CNN. However, CNN was the most trusted news source for Democrats and Fox News was their most distrusted outlet (Jurkowitz et al, 2020; see also Hoewe et al, 2023). Source attribution to prominent news sources, such as CNN and Fox News, has been regarded as an important shortcut for exposure and avoidance of news stories, as well as for the perceptions of those reports once accessed.…”
Section: Introductionmentioning
confidence: 99%